Full Day School dalam tinjauan Psikologi, Sosiologi, dan Ekonomi Pendidikan - Abdan Rahim (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
Full day school comes from English Language. It means that full day school is a school which held in a day or education program that the activities held in school from morning to afternoon. The essential meaning of full day school is not only add the time and give more learning materials. This policy raise pros and cons between education expert and the society as a subject and object in education. Nevertheless in the perspective of local wisdom, this program is one of institution which can solve moral decline in the country, since in fact it also apply the comprehensive teaching and learning activity. The discourse about FDS has got people’s attention, even it become polemic pros and cons among society, although the purpose of FDS is to built the better students’ character, it also help students’ parents who work full in a day and do not have time to handle their children, and parents able to prevent students’ activity from negativity or reduce negative influence outside from school, however there are some people who disagree with this plan.